A percepção de qualidade de vida pelos idosos da Universidade Aberta para Maturidade - UNABEM - UEMG/Passos-MG - Peixoto, Nádia (2015)
Longevity is a reality that needs to be considered with relevance for all segments of society, once the elderly population has grown dramatically in the social pyramid. Maturity university programs have been an important factor in health promotion of elderly inserted into living programs. This study aimed at knowing the perceptions about quality of life of elderly participants of an Open University for Maturity (Universidade Aberta para Maturidade - UNABEM) in Passos, Minas Gerais, Brazil. It is a quali-quantitative, descriptive study with cross-sectional design. The sample consisted of 90 elderly, being 75 female and 15 male. The instruments used were: a socio-demographic questionnaire with gender, age, marital status, education, housing, income and religion variables, and the questionnaires WHOQOL - bref and WHOQOL- old, both developed by the group of studies of quality of life in the World Health Organization, translated and validated in Brazil. Statistical analysis data were performed by descriptive analysis. The significance level was set at 5% (α = 0.05). The data analysis indicated that the participants of UNABEM, are mostly female, but both sexes aging 60 to 69 years old; married, with a high school level education. Most of them lived with their families, with income between one and two national minimum wages and were Catholics. The participants saw their quality of life as "very good" or "good" and are satisfied with their health. The Social Relations domain (WHOQOL - bref) and the Social Participation facet (WHOQOL - old) are the ones that achieved higher scores in relation to the perception of quality of life. The Environment domain (WHOQOL - bref) and Death and Dying facet (WHOQOL - old) were the lowest score in relation to the perception of quality of life. In order to identify the statistically significant difference of socio-demographic variables on the perception of quality of life, the 90 participants were grouped again forming subgroups and compared regarding the scores in each domain and facet. They had statistically significant higher scores: elderly participants of both sexes aging 70 to 79 in the Environment and Social relation Domains compared to those aging 60 to 69 years old; the widowers in the physical and autonomy domains compared to the married ones. The elderly who completed high school in the physical domain compared to the elderly who completed junior high school and compared to those who had not finished junior high school in the psychological domain and in the total score. The elderly who live alone in the physical and in the total score compared to those who had a partner; the elderly who live with their families in the total and autonomy domain compared to those who lived with a partner. Elderly participants who earned more than three minimum wages, in the Environment domain, compared to those who earn three minimum wages. Finally, the male participants in the Physical and Psychological domains and Death and Dying facets. It is concluded that the elderly participating at UNABEM had a better perception of a quality of life regarding the social aspects and considered the active aging an important aspect to the quality of life.